Using social networking technology to develop intercultural communicative competence: a case of GCSE Mandarin. Issue 4 (7th August 2020) - Ruan, Jingjing; Medwell, Jane
ABSTRACT: The research reported in this article aimed to explore how social networking technology might contribute to the development of intercultural communicative competence of learners of Chinese as a foreign language. The research involved a longitudinal exploratory case study, in which the case was a single General Certificate of Secondary Education Mandarin class of nine learners in a comprehensive secondary school in the Midlands of the UK. Methods of data collection included participant observation, field notes, questionnaires and semi-structured interviews with students. A Community of Inquiry analysis framework was adapted and used as the basis of coding and analysis of students' online behaviours. The findings of this study showed that Social Presence was the category of presence most often identified in the current Community of Inquiry, followed by Cognitive Presence, and then Teaching Presence. The social networking tools created a Community of Inquiry that provided extra input of Chinese language and culture that motivated learners to become global citizens and intercultural speakers. However, this study also found that although all students had full access to social networking technology, their uses of these tools were uneven.